Persepsi dan Preferensi Konsumen Kosmetik Halal - Tamira Naila Rafifasha; Nurfahmiyati (UNISBA Press, 2022)
Abstract. In choosing the product to be used, as a Muslim, you must prioritize halal (1). Likewise, the cosmetic products we use must be halal (2). In Surah An-Nahl verse 114 that Allah commands humans to consume halal food, this can be analogous to products other than food, including cosmetics. The purpose of this study is to find out how the perceptions and preferences of consumers of halal cosmetics Make Over in the city of Bandung, and to find out how the preferences of consumers of halal cosmetics make over in an Islamic perspective in the city of Bandung. This research method is a qualitative method. This type of research is a case study. Sources of data used in this study is primary data with interview analysis method. The results showed that: (1) Consumers' perceptions and preferences in using Make Over cosmetics because they are of good quality, durable, and do not irritate the skin. Consumers are interested in using products based on social media information, and beauty vlogger reviews. Consumers prioritize their needs, because they are for personal interests. Consumers in buying cosmetics based on attractive packaging, and affordable product prices. (2) Consumer preferences of Make Over cosmetics in an Islamic perspective, based on the composition contained in a product, as well as the halal label listed on the packaging. In Islam, it has also been explained that halal products must be used. In Islam teaches to consume everything as needed, because anything in excess is not good. This is in line with the word of Allah Q.S al-A'raf verse 31 which means